Changes in EU Food Supply and the Activities of the European Platform for Action on Diet, Physical Activity and Health - Ewa Halicka; Joanna Kaczorowska; Krystyna Rejman (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This paper presents the changes in food supply in selected EU Member states and average EU+ after the establishment of the European Platform for Action in the field of Diet, Physical Activity and Health in 2005. The per capita annual supply of vegetables, fruits, pulses, sugar & sweeteners and the daily values of calories and fat are analysed based on FAO Food Balance Sheet (FBS) data. The supply of vegetables in the EU has decreased since 2005 while that of fruits, pulses and sugar & sweeteners, as well as energy and fat have not changed significantly. The 313 voluntary commitments of Platform members, aimed at promoting healthier food choices and life styles in the region do not seem to have had a significant impact on food supply at population level. Firmer policy measures, incl. fiscal regulations are needed to support these voluntary actions. Sustainability issues should be included in the health-oriented initiatives as food choices contribute not only to the health of individuals but also of the environment as a whole.